Teaching foreign students of professional dialogical communication - Сенік, Лілія Миколаївна; Рагріна, Жанна Михайлівна; Лебеденко, Ірина Леонідівна (Stockholm : Liber A, 2020)
It is known that the ultimate goal of teaching a foreign language is the formation of communicative competence, i.e. development of communication skills in this language. When teaching communication, the central task of the educational process in language departments becomes communicative and speech activity. In the methodology of teaching a language as a foreign, the opinion about the need for a reasonable correlation between the communicative orientation of instruction and the conscious systematization of language material was firmly established. It is generally accepted that the linguistic means necessary for the implementation of a communicative and practical goal are selected and implemented on a functional basis. These principles acquire particular significance in connection with the transition of Ukrainian universities to the English-language form of education.